VISUAL-INFORMATIONAL COMMUNICATIONS OF THE INCLUSIVE ENVIRONMENT: DESIGN-EDUCATIONAL NARRATIVE - ЯКОВЕЦЬ, І. О.; Чепелюк, О. В.; Луговський, О. Ф.; Чугай, Н. М. (Art and Design, 2023)
Purpose: study of factors influencing formation of visual information communications of inclusive environment and determination of the role of design education in these processes. Methodology. A systematic approach was used in the scientific research in order to achieve the purpose. This enabled to consider the dynamic transformations of visual information communications as a holistic phenomenon that forms a field for communication with the environment and people and is capable to adapt. In this study, adaptation is associated with formation of an inclusive environment. When considering examples of practical activities, the analytical method was used, as well as the methods of figurative and stylistic analysis and comparative analysis. The results. The study has shown what mechanisms are involved in the introduction of changes in the visual and information environment and what these processes are connected with. The scale of such changes is determined by a state policy based on developing of a course of ideological and cultural education of a society ready to perceive visual attitudes and capable of perceiving objects of the subject-spatial environment as a visual text. It is noted that there is a need to develop the design of an international sign language for establishing a "human-environment" communication in an inclusive space. It is a designer who has to deal with new challenges, a designer capable to distinguish visually significant forms and aware of the idea that all his activity is a kind of visualization. Therefore, at the stage of training in design educational institutions, a designer should develop visual attitudes and visual values. The way it could be implemented in practice has been demonstrated on the materials of works of design students of Cherkasy State Technological University, Kherson National Technical University and Jan Matejka Academy of Fine Arts in Krakow (Poland). Scientific novelty. It is for the first time that works of Ukrainian and one EU country (Poland) representatives of design-education environment have been taken and considered in order to analyze practical experience in the field of visual information communication of an inclusive environment. Practical significance. The study reveals design approaches for solving artistic tasks in developing visual information communication systems in an inclusive environment, providing for ergonomic components and resulting in creating of certain aesthetic characteristics of the objects designed.